NUTRITIONAL STATUS PROFILE OF SCHOOLCHILDREN AGED 6 TO 18 YEARS: A CASE STUDY AT SESI-SP (Fiep Bulletin - online, 2016)
The objective of this study was to evaluate the profile of the nutritional status of six school units of SESI-SP Araçatuba and its jurisdiction. The descriptive data analysis involved 2,653 students aged between 6 and 18 years old. The variables obtained were: age, sex, weight, height, body mass index (BMI) and school units. The classification of nutritional status was performed in AnthroPlus ® program using BMI-for-age, according to the bows from the World Health Organization 2006/2007. About 40% of the students were overweight. There was no association between the nutritional status and the school units (p = 0.71). There was a higher frequency of overweight in males (43.42%%) than in females (36.68%) (p
Keywords: Nutritional status; obesity; school health.